Probing the neurochemical basis of synaesthesia using psychophysics - Terhune, Devin B.; Song, Seoho M.; Duta, Mihaela D.; Cohen Kadosh, Roi (Frontiers in Human Neuroscience, 2014)
The neurochemical mechanisms that contribute to synaesthesia are poorly understood, but multiple models implicate serotonin and GABA in the development of this condition. Here we used psychophysical tasks to test the predictions that synaesthetes would display behavioural performance consistent with reduced GABA and elevated serotonin in primary visual cortex. Controls and synaesthetes completed the orientation-specific surround suppression (OSSS) and tilt-after effect (TAE) tasks, previously shown to relate to GABA and serotonin levels, respectively. Controls and synaesthetes did not differ in the performance parameter previously associated with GABA or in the magnitude of the TAE. However, synaesthetes did display lower contrast difference thresholds in the OSSS task than controls, but only when no surround was present. These results are inconsistent with the hypothesized roles of GABA and serotonin in this condition, but provide preliminary evidence that synaesthetes exhibit enhanced contrast discrimination.